Hubungan Adekuasi Hemodialisis terhadap Kualitas Hidup, Kecemasan, dan Status Gizi Pasien Ginjal Kronis di RSUD Provinsi NTB - Nur Raihan Ramdhani; Lalu Buly Fatrahady Utama; I Gede Angga Adnyana; Irwan Setiobudi (Universitas Malahayati Lampung, 2026)
ABSTRACT Chronic kidney disease is a global health problem with a continuously increasing prevalence. In the end stage, patients require long-term hemodialysis therapy, in which hemodialysis adequacy plays an important role in controlling uremic symptoms and influencing patients’ quality of life, anxiety levels, and nutritional status. This study aimed to analyze the relationship between hemodialysis adequacy and quality of life, anxiety, and nutritional status among chronic kidney disease patients undergoing hemodialysis at the Provincial General Hospital of West Nusa Tenggara in 2025.This study employed a quantitative method with an observational analytic design. The sampling technique used was purposive sampling, involving 90 chronic kidney disease patients undergoing hemodialysis. Data were analyzed using the Chi-square test with a significance level of p-value 0.05.The results showed that the majority of patients had adequate hemodialysis adequacy, totaling 72 respondents (60.0%), good quality of life in 68 respondents (56.7%), mild anxiety levels in 70 respondents (58.3%), and normal nutritional status in 65 respondents (54.2%). The Chi-square test indicated a significant relationship between hemodialysis adequacy and quality of life (p-value = 0.003), anxiety level (p-value = 0.001), and nutritional status (p-value = 0.004).In conclusion, hemodialysis adequacy is significantly associated with quality of life, anxiety levels, and nutritional status among chronic kidney disease patients at the Provincial General Hospital of West Nusa Tenggara in 2025. Keywords: Quality of Life, Chronic Kidney Disease, Gender, Self-Efficacy, Therapy Adherence. ABSTRAK Penyakit ginjal kronis merupakan masalah kesehatan global dengan prevalensi yang terus meningkat. Pada stadium akhir, pasien memerlukan terapi hemodialisis jangka panjang, di mana adekuasi hemodialisis berperan penting dalam mengendalikan gejala uremia serta memengaruhi kualitas hidup, tingkat kecemasan, dan status gizi pasien. Tujuan penelitian adalah menganalisis hubungan adekuasi hemodialisis terhadap kualitas hidup, kecemasan, dan status gizi pasien ginjal kronis yang menjalani hemodialisis di RSUD Provinsi Nusa Tenggara Barat tahun 2025.Metode penelitianinikuantitatif dengan desain analitik observasional. Teknik pengambilan sampel dilakukan dengan purposive sampling dengan jumlah sampel sebanyak 90 pasien ginjal kronis yang menjalani hemodialisis. Data dianalisis menggunakan uji Chi-square dengan batas nilai signifikansi p-value 0,05. Hasil penelitian menunjukkan bahwa sebagian besar pasien memiliki adekuasi hemodialisis yang adekuat sebanyak 72 responden (60,0%), kualitas hidup baik sebanyak 68 responden (56,7%), tingkat kecemasan ringan sebanyak 70 responden (58,3%), serta status gizi normal sebanyak 65 responden (54,2%). Uji Chi-square menunjukkan adanya hubungan signifikan antara adekuasi hemodialisis dengan kualitas hidup (p-value = 0,003), tingkat kecemasan (p-value = 0,001), dan status gizi (p-value = 0,004). Kesimpulan penelitian ini adalah adekuasi hemodialisis berhubungan signifikan dengan kualitas hidup, tingkat kecemasan, dan status gizi pasien ginjal kronis di RSUD Provinsi NTB tahun 2025. Kata Kunci: Adekuasi Hemodialisis, Penyakit Ginjal Kronik, Kualitas Hidup, Kecemasan, Status Gizi.